Negative plate and lithium ion secondary battery
By increasing the silicon content in the negative electrode sheet and controlling the structure of siliceous carbon material and negative current collector, the problem of fracture and crushing of the negative electrode current collector in high-energy-density lithium-ion batteries is solved, and the high energy density and long cycle life of the battery are achieved.
Patent Information
- Application Number
- CN202411995739.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
AI Technical Summary
The existing high-energy density lithium-ion batteries have a high risk of breaking and crushing the negative electrode current collector during the circulation process, which affects the cycle life of the battery.
By increasing the silicon content in the negative electrode sheet and adjusting the silicon doped amount, the particle size of the silicon carbon material and the intensity of specific diffraction peaks in the XRD diffraction pattern of the negative electrode current collector, the adaptability between the silicon carbon material and the negative electrode current collector is improved, and the extrusion failure of the negative electrode current collector by the silicon carbon material is reduced.
While ensuring high energy density, it can effectively improve the fracture and crushing problem of the negative electrode current collector during the circulation process and improve the cycle life of the battery.
Smart Images

Figure CN119890220A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a lithium ion secondary battery comprising the negative electrode sheet. Background Art
[0002] Lithium-ion batteries have great potential in electronic devices, electric vehicles, etc. Current technology is committed to improving the energy density of batteries. Silicon-based materials are considered to be key materials for improving battery energy density because they have a higher theoretical specific capacity (about 3600mAh / g), which is much higher than the theoretical specific capacity of graphite materials (about 370mAh / g). The current method to improve battery energy density is mainly to increase the silicon content and compaction density of the negative electrode sheet. However, with the increase of silicon content and compaction density of the negative electrode sheet, the risk of fracture and crushing of the negative electrode current collector during the battery charge and discharge cycle is greatly increased.
[0003] Therefore, it is very important to improve the problem of negative electrode current collector breakage and crushing during the cycle of high energy density batteries. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem of fracture and crushing of the negative electrode current collector in the high energy density battery in the prior art during the cycle process, and provide a negative electrode sheet and a lithium ion secondary battery including the negative electrode sheet. The negative electrode sheet of the present invention has a high silicon content (for example, the mass content of element Si in the negative electrode active coating is 1.5%-15.5%), and by adjusting the silicon content, the particle size of the silicon-carbon material and the intensity of the specific diffraction peak in the XRD (X-Ray Diffraction) diffraction spectrum of the negative electrode current collector, the silicon-carbon material and the negative electrode current collector are highly compatible, and the extrusion damage of the silicon-carbon material to the negative electrode current collector can be reduced while ensuring a high silicon content, so that the lithium ion secondary battery (hereinafter referred to as the battery) including the negative electrode sheet has a high energy density and effectively improves the problem of fracture and crushing of the negative electrode current collector during the cycle process, thereby improving the cycle life of the battery.
[0005] In order to improve the energy density of the battery, the simplest and most effective method is to increase the silicon content in the negative electrode sheet and increase the compaction density of the negative electrode sheet. However, since the hardness of silicon-carbon materials is greater than that of graphite materials, if the content of silicon-carbon materials in the negative electrode sheet is increased or the compaction density of the negative electrode sheet is increased, the extrusion stress of silicon-carbon particles on the negative electrode current collector will increase, thereby greatly increasing the risk of fracture and crushing of the negative electrode current collector. After a lot of research, the inventors of the present invention have found that the appropriate silicon-carbon material particle size can increase the compaction density of the negative electrode sheet while ensuring that the silicon-carbon material does not cause serious extrusion to the negative electrode current collector. Therefore, by adjusting the average particle size of the silicon-carbon material, the energy density of the battery can be improved, and the extrusion problem of the silicon-carbon material on the negative electrode current collector can be improved to a certain extent.
[0006] However, it is not enough to only regulate the average particle size of silicon-carbon materials. With the increase of silicon doping in the negative electrode sheet, the extrusion stress of silicon-carbon materials on the negative electrode current collector is significantly increased. At this time, it is also necessary to simultaneously regulate the compressive strength of the negative electrode current collector so that the two match each other, so as to further solve the problem of the rupture and crushing of the negative electrode current collector in the battery cycle of high silicon-doped batteries. In the XRD diffraction pattern of the negative electrode current collector, the intensity ratio of the 111 crystal plane peak to the 200 crystal plane peak can characterize the compressive strength of the negative electrode current collector. By regulating the ratio of the two, the crystal plane orientation and crystal plane competition of the negative electrode current collector can be regulated, thereby improving the compressive strength of the negative electrode current collector. The higher the ratio of the two, the higher the compressive strength of the negative electrode current collector. The higher the compressive strength, the more resistant the negative electrode current collector is to pressure, and it is not easy to break and crush when squeezed by the silicon-carbon material with greater hardness. However, the compressive strength of the negative electrode current collector should not be too high. When the tensile strength is too high, the elongation of the negative electrode current collector will decrease, thereby affecting the extension of the negative electrode sheet in the X-axis and Y-axis directions (i.e., the length and width directions of the battery), causing the negative electrode active materials to squeeze each other, causing expansion in the Z-axis direction (i.e., the thickness direction of the battery), increasing the thickness expansion rate, and affecting the battery life. Therefore, it is necessary to coordinately regulate the tensile strength of the negative electrode current collector, the particle size of the primary spherical particles of the silicon-carbon material, and the silicon doping amount. When all three meet a specific range, the negative electrode sheet can have a high silicon doping amount while effectively improving the problem of the negative electrode current collector breaking and crushing during the cycle.
[0007] Based on this, the inventor of the present invention proposed the following solution:
[0008] The first aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active coating located on at least one side of the surface of the negative electrode current collector, the negative electrode active coating comprising a negative electrode active material; the negative electrode active material comprises a silicon-carbon material; the silicon-carbon material comprises primary spherical particles; the mass content c of element Si in the negative electrode active coating is 1.5%-15.5%; the average particle size d of the primary spherical particles is 1μm-6μm; the negative electrode current collector comprises Cu, and the XRD diffraction spectrum of the negative electrode current collector has a 111 peak at 2θ of 42.5°-44.5°, a 200 peak at 2θ of 49°-52°, and the intensity of the 111 peak is I 111 , the intensity of the 200 peak is I 200 ;I 111 / I 200 Is 1-10.
[0009] A second aspect of the present invention provides a lithium ion secondary battery, wherein the lithium ion secondary battery comprises the negative electrode sheet described in the first aspect of the present invention.
[0010] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0011] (1) The negative electrode sheet of the present invention has a higher silicon doping content and compaction density.
[0012] (2) The battery of the present invention has high energy density and long cycle life.
[0013] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Shown is the XRD diffraction pattern of the negative electrode current collector in one example of the present invention.
[0015] Figure 2 Shown is a scanning electron microscope (SEM) image of a cross section of a negative electrode sheet along the thickness direction in an example of the present invention.
[0016] Figure 3 FIG. 1 is a schematic diagram (top view) of a groove on the surface of a negative electrode sheet in an example of the present invention, wherein: Figure 3 (a) The grooves are arranged continuously; Figure 3 (b) The grooves are arranged in sections.
[0017] Figure 4 FIG. 1 is a schematic diagram of the width of a groove in an example of the present invention, wherein Figure 4 (a)- Figure 4 The two long sides of the groove in (c) are straight lines. Figure 4 The two long sides of the groove in (d) are curved lines.
[0018] Figure 5 FIG. 1 is a schematic diagram of the spacing of grooves in an example of the present invention, wherein Figure 5 (a) is the case where two adjacent long sides are straight and parallel. Figure 5 (b) is the case where two adjacent long sides are straight lines and not parallel. Figure 5 (c) is the case where two adjacent long sides are curved lines.
[0019] Figure 6 FIG. 1 is a schematic diagram showing the structure of a winding core in an example of the present invention.
[0020] Figure 7 The figure shows a schematic diagram of the structure of the positive electrode sheet in an example of the present invention, wherein Figure 7 (a) is a top view, Figure 7 (b) is a cross-sectional view along the thickness direction.
[0021] Figure 8 FIG. 1 is a schematic top view of the first surface of a positive electrode sheet in an example of the present invention. DETAILED DESCRIPTION
[0022] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0023] A first aspect of the present invention provides a negative electrode sheet, which may include a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector. The negative electrode active coating may include a negative electrode active material, and the negative electrode active material may include a silicon-carbon material. The silicon-carbon material includes primary spherical particles. The silicon-carbon material refers to a composite material including elemental carbon and elemental silicon, for example, a material formed by silicon and / or oxidized silicon filling (including partial filling or complete filling) in the pores of porous carbon.
[0024] In the present invention, the mass content c of element Si in the negative electrode active coating can be 1.5%-15.5%, for example, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or 15.5%.
[0025] In one example, the mass content c of element Si in the negative electrode active coating is 3%-11%.
[0026] In one example, the mass content c of element Si in the negative electrode active coating is 3.5%-10.5%.
[0027] In the present invention, the mass content c of the element Si in the negative electrode active coating can be obtained by testing by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and then soaked in dimethyl carbonate (DMC) solvent for 12 hours, and then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and then the negative electrode sheet is treated at 400°C in an inert atmosphere for 2 hours (for example, in a tube furnace, nitrogen or argon atmosphere), and the negative electrode active coating can be peeled off from the negative electrode current collector, and the negative electrode active coating is collected as a test sample. Using a thermogravimetric analyzer (for example, TGA 550 thermogravimetric analyzer), the test sample amount is 5mg-15mg, and the temperature is increased from room temperature (25°C) to 900°C at a heating rate of 10°C / min in an air or oxygen atmosphere, and kept at 900°C for 40min, so that the non-silicon components in the negative electrode active coating are volatilized and the silicon can be fully oxidized to silicon dioxide. The remaining substance is the ash of the negative electrode active coating. The mass content of element Si in the negative electrode active coating can be calculated based on the mass of the ash. The calculation formula is as follows: mass content of element Si in the negative electrode active coating = 7×mass of ash / (15×mass of test sample).
[0028] In the present invention, the average particle size d of the primary spherical particles may be 1 μm-6 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or 6 μm.
[0029] In one example, d is 3 μm-5 μm.
[0030] In the present invention, the average particle size d of the primary spherical particles can be tested and obtained by conventional methods in the art, for example, after discharging the battery to 0% SOC, dismantling and removing the negative electrode sheet, soaking it in DMC solvent for 12 hours, and then rinsing it with DMC solvent to remove the lithium salt attached to the negative electrode sheet, using an argon ion milling instrument CP laser to cut the negative electrode sheet, and then using a scanning electron microscope (SEM) to observe (using the high voltage mode (Back-scattered Electrons BSE)). In this mode, the contrast of the silicon-carbon material is brighter (which can be used to distinguish the graphite material and the conductive agent in the negative electrode active coating). Measure at a magnification of 5K, randomly select at least 20 primary spherical particles, measure the particle size of each primary spherical particle, and take the average value. If the number of primary spherical particles is less than 20 at a magnification of 5K, take another mirror image until 20 primary spherical particles are measured.
[0031] In the present invention, the negative electrode current collector includes Cu, and the XRD diffraction pattern of the negative electrode current collector has a 111 peak at 2θ of 42.5°-44.5° (for example, 42.5°, 43°, 43.1°, 43.2°, 43.3°, 43.4°, 43.5°, 43.6°, 43.7°, 43.8°, 43.9°, 44° or 44.5°), and a 200 peak at 2θ of 49°-52° (for example, 49°, 49.5°, 50°, 50.1°, 50.2°, 50.3°, 50.4°, 50.5°, 50.6°, 50.7°, 50.8°, 50.9°, 51°, 51.5° or 52°), and the intensity of the 111 peak is I 111 , the intensity of the 200 peak is I 200 I 111 / I 200 It can be 1-10, for example, 1, 1.5, 2, 3, 4, 5, 6, 7, 8, 9 or 10. In the manufacturing process of the negative electrode current collector, by adding additives, its microstructure such as grain size, morphology, orientation and internal stress can be optimized, so as to achieve controllable production of high mechanical properties of the negative electrode current collector.
[0032] In one example, I 111 / I 200 It is 3-6.9.
[0033] In the present invention, the intensity of the 111 peak is 111 and the intensity of the 200 peak is I 200 It can be tested by conventional methods in the art, for example, after discharging the battery to 0% SOC, dismantling and removing the negative electrode sheet, taking the empty foil area at the head (or tail) (i.e., the part without the negative electrode active coating on the negative electrode current collector), soaking it in DMC solvent for 12 hours, and then rinsing it with DMC solvent to remove the lithium salt attached to the empty foil area; after drying, using an X-ray powder diffraction instrument (such as Shimadzu XRD-6100 X-ray diffractometer) to test the surface of either side of the negative electrode current collector, and obtain the intensity of the diffraction peak 111 at 2θ located at 42.5°-44.5° and the diffraction peak 200 at 2θ located at 49°-52°. Figure 1 The XRD diffraction pattern of the negative electrode current collector in one embodiment of the present invention is shown. It can be seen from the figure that there is a 111 peak at 2θ of 42.5°-44.5° and a 200 peak at 2θ of 49°-52°. The intensity of the 111 peak is 111 The intensity of the 200 peak I 200 The ratio I 111 / I 200 About 3.9.
[0034] In the present invention, the mass content c of the element Si in the negative electrode active coating, the average particle size d of the primary spherical particles and the intensity I of the 111 peak are 111 The intensity of the 200 peak I 200 The ratio satisfies: 5≤(I 111 / I 200 ) / (c×d)≤85, for example, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80 or 85.
[0035] In one example, 7.3≤(I 111 / I 200 ) / (c×d)≤50.5.
[0036] In the present invention, the mass content of element Si in the silicon-carbon material can be 30%-80%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%.
[0037] In the present invention, the surface density of the negative electrode sheet is m, and the unit is mg / cm 2 The compaction density of the negative electrode sheet is y, in g / cm 3 ; m and y satisfy: 6.5≤m×y≤13, for example, 6.5, 7, 8, 9, 10, 11, 12 or 13.
[0038] In one example, 9.6≤m×y≤9.9.
[0039] Improving the compaction density or surface density of the negative electrode sheet is an effective way to improve the overall energy density of the battery. Therefore, in theory, the most effective way to improve the energy density of the battery is to simultaneously increase the compaction density and surface density of the negative electrode sheet. However, in the actual production process, due to the characteristics of the negative electrode active material itself, the gaps between the negative electrode active material particles, and the expansion of the binder between the particles after absorbing the electrolyte, the expansion of the negative electrode active coating becomes larger and larger as the surface density of the negative electrode sheet increases after the battery is charged and discharged, resulting in a large rebound in thickness and failure to achieve the expected compaction. Therefore, when it exceeds a certain range, the more the surface density is increased, the more the compaction density will decrease, and the two cannot be effectively taken into account. If the pressure of the negative electrode sheet during the rolling process is forcibly increased under the premise of a large surface density, the graphite material will break and fail, resulting in capacity loss and lithium precipitation, which will reduce the energy density of the battery. Therefore, there is a certain mutually restrictive relationship between compaction density and surface density. It is necessary to simultaneously regulate the surface density and compaction density of the negative electrode sheet so that the two meet a specific relationship. At this time, the battery has a better energy density and cycle life. When m×y is too small (for example, less than 6.5), the energy density of the battery is low; and when m×y is too large (for example, greater than 13), the negative electrode active material may be broken, thus affecting the cycle life of the battery.
[0040] In the present invention, the surface density m of the negative electrode sheet can be 5-8, in units of mg / cm 2 ; For example, 5mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 or 8mg / cm 2 .
[0041] In the present invention, the surface density m of the negative electrode sheet can be tested by conventional methods in the art. For example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and then soaked in DMC solvent for 12 hours, and then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, dried, and the residue on the surface of the negative electrode sheet is washed with deionized water. After drying, the negative electrode sheet is punched into a disc with a diameter of 44.3 mm using a punching mold, 10 discs are taken, the mass of each disc is weighed, and the average value is taken, which is M (in mg), then m=(M-m1)×100 / 1540.25, wherein m1 is the mass of the negative electrode collector in the disc, in mg.
[0042] In the present invention, the compaction density y of the negative electrode sheet can be 1.35-1.6, in g / cm 3 ; For example, 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm3 , 1.55g / cm 3 or 1.6 g / cm 3 The compaction density here refers to the compaction density actually measured after the battery is disassembled and the negative electrode sheet is taken out during the battery preparation process. It is different from the compaction density obtained by rolling the negative electrode sheet during the battery preparation process. This is because after the negative electrode sheet is assembled into a battery, there will be physical and chemical rebound, resulting in compaction rebound, making the compaction density of the negative electrode sheet actually measured after the battery preparation is completed smaller than the compaction density obtained after rolling.
[0043] In the present invention, the compaction density y of the negative electrode sheet can be tested by conventional methods in the art. For example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and then soaked in DMC solvent for 12 hours, and then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and dried. At least 20 sites are selected on the negative electrode sheet, and the thickness of the negative electrode sheet at each site is measured using a micrometer, and the average value is Y (in μm). Then the compaction density y=m×20 / (Y-thickness of the negative electrode collector), where the thickness of the negative electrode collector is in μm.
[0044] In the present invention, the silicon-carbon material may further include secondary spherical particles formed by a plurality of the primary spherical particles. The “several” means that the number of the primary spherical particles forming the secondary spherical particles is greater than or equal to 2. Figure 2 The figure shows a scanning electron microscope (SEM) image of a cross section of a negative electrode sheet in an example of the present invention along the thickness direction. It can be seen from the figure that the silicon-carbon material includes primary spherical particles and secondary spherical particles formed by a plurality of primary spherical particles. Among them, the black circle frame in the figure is the primary spherical particle, and the black square frame is the secondary spherical particle.
[0045] The conventionally used silicon-carbon material is in block form, and the average particle size is about 6μm-12μm. Therefore, the conventionally used silicon-carbon particles have poor conductivity and it is difficult to achieve a large compaction density. The energy density improvement is limited and is not suitable for battery systems with high silicon doping (for example, the silicon content in the negative electrode active coating reaches more than 5%). In the present invention, a silicon-carbon material including primary spherical particles is used as the negative electrode active material. Primary spherical particles with smaller particle sizes are beneficial to improving the energy density of the battery; however, due to their smaller particle size and larger specific surface area, the risk of side reactions with the electrolyte is correspondingly increased, and the stability is poor. In order to reduce the occurrence of side reactions between the silicon-carbon material and the electrolyte, secondary spherical particles composed of several primary spherical particles are further added. Secondary spherical particles with larger particle sizes have a smaller specific surface area, so they have a lower risk of side reactions with the electrolyte and better stability.
[0046] In the present invention, the average particle size D of the secondary spherical particles can be 3μm-20μm, for example, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.
[0047] In one example, the average particle size D of the secondary spherical particles is 7.5 μm-11 μm.
[0048] In the present invention, the average particle size D of the secondary spherical particles can be obtained by testing conventional methods in the art, for example, after discharging the battery to 0% SOC, disassembling and removing the negative electrode sheet, soaking it in DMC solvent for 12 hours, and then rinsing it with DMC solvent to remove the lithium salt attached to the negative electrode sheet, using an argon ion milling instrument CP laser to cut the negative electrode sheet, and then using SEM to observe (using high voltage mode), measuring at a magnification of 5K, randomly selecting at least 20 secondary spherical particles, measuring the particle size of each secondary spherical particle, and taking the average value. If the number of secondary spherical particles is less than 20 at a magnification of 5K, then take a mirror image again until 20 secondary spherical particles are measured.
[0049] In the present invention, the sphericity of the primary spherical particles may be 0.7-1, for example, 0.7, 0.8, 0.9 or 1.
[0050] In one example, the primary spherical particles have a sphericity of 0.8-0.95.
[0051] In the present invention, the sphericity of the primary spherical particles can be tested by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and then the negative electrode active coating is rinsed off from the negative electrode current collector with deionized water, and the filtrate is removed by centrifugation after ultrasound, and dried. The obtained powder is observed with SEM (using high voltage mode). The image of the primary spherical particles in the SEM mirror image at a certain magnification (for example, 2500 times) is analyzed by image processing software (such as Image Pro Plus), and at least 10 primary spherical particles of silicon-carbon material in the mirror image are selected to obtain the perimeter and area of each particle, and the perimeter equivalent radius and area equivalent radius are calculated respectively, then the sphericity = area equivalent radius / perimeter equivalent radius, and the average value is taken.
[0052] In the present invention, in the negative electrode active coating, the amount of the primary spherical particles accounts for 0.1-0.9 of the total amount of the primary spherical particles and the secondary spherical particles, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9.
[0053] In one example, in the negative electrode active coating, the amount of the primary spherical particles accounts for 0.35-0.8 of the total amount of the primary spherical particles and the secondary spherical particles.
[0054] By adjusting the quantitative ratio of primary spherical particles and secondary spherical particles in silicon-carbon materials, the battery can further balance high energy density and good cycle stability. This is because: after mixing primary spherical particles and secondary spherical particles in a specific quantitative ratio, the silicon-carbon material can be arranged more tightly, which is not only beneficial to improve the conductivity of the silicon-carbon material itself, but also to improve the compaction of the negative electrode sheet, so that the silicon content in the negative electrode active coating reaches more than 5%, thereby improving the energy density of the battery. And when primary spherical particles and secondary spherical particles are mixed in a specific quantitative ratio, the risk of side reactions between silicon-carbon materials and electrolytes can be reduced, which is beneficial to improving the cycle stability of the battery.
[0055] In the present invention, in the negative electrode active coating, the number of the primary spherical particles and the number of the secondary spherical particles can be tested and obtained by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and the negative electrode sheet is cut along the thickness direction of the negative electrode sheet using an argon ion milling instrument CP laser, and then a SEM (high voltage mode) is used to obtain a mirror image of the cross section of the negative electrode sheet along the thickness direction, and observed at a magnification of 1K, and at least 20 mirror images of different cross sections are selected, and the number of primary spherical particles and the number of secondary spherical particles in each mirror image are counted respectively, and the average value is taken.
[0056] In the present invention, the negative electrode active material may further include a graphite material. The graphite material includes, for example, artificial graphite and / or natural graphite. The graphite material includes secondary particles. The secondary particles are formed by a plurality of primary particles. The “several” means that the number of the primary particles forming the secondary particles is greater than or equal to 2.
[0057] In the present invention, the average particle size d2 of the secondary particles can be 6μm-20μm, for example, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.
[0058] In one example, d2 is 10 μm-15 μm.
[0059] The inventors of the present invention further discovered that by using a specific graphite material in combination and regulating the structure and particle size of the graphite material, the graphite material includes secondary particles formed by primary particles, and the average particle size of the secondary particles is 6μm-20μm, which can further improve the energy density of the battery. The secondary particles of the graphite material with a specific particle size can improve the energy density of the battery compared with the graphite material of the primary particles. Therefore, the graphite material has a high degree of matching with the specific silicon-carbon material, which is conducive to the improvement of the energy density of the battery.
[0060] In the present invention, the average particle size d2 of the secondary particles can be obtained by testing by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and then the negative electrode active coating is rinsed off from the negative electrode current collector with deionized water, and the filtrate is removed by centrifugation after ultrasonication, and dried, and the obtained sample is dispersed in deionized water containing nonylphenol polyoxyethylene ether (wherein the mass content of nonylphenol polyoxyethylene ether is 0.02%-0.03%) to form a mixture, ultrasonicated for 2 minutes, and then tested using a Malvern particle size tester, and the median particle size Dv50 data obtained is the average particle size d2 of the secondary particles. Due to the specific composition and particle size of the graphite material and the silicon-carbon material in the present invention, the silicon-carbon material has little effect on the average particle size of the secondary spherical particles of the graphite material, and therefore, the data obtained by the above-mentioned test method is the average particle size of the secondary particles.
[0061] In the present invention, the ratio of the average particle size d2 of the secondary particles to the average particle size d of the primary spherical particles is 1.33≤d2 / d≤20, for example, 1.33, 1.5, 1.67, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20.
[0062] In one example, 2≤d2 / d≤10.7.
[0063] In one example, 2.1≤d2 / d≤4.6.
[0064] For high silicon-doped battery systems, the advantages of high silicon-doping can be maximized by ensuring high compaction and low expansion of the negative electrode sheet. Therefore, the silicon-carbon material is mixed with a graphite material having secondary particles. When the ratio of the average particle size of the secondary particles to the average particle size of the primary spherical particles is within a specific range, the graphite material and the silicon-carbon material are matched to make the orientation consistency of the negative electrode active material better, which is beneficial to reduce the cycle expansion rate of the negative electrode sheet. When d2 / d is too large (for example, greater than 20), the particle size of the secondary graphite particles is too large relative to the particle size of the primary silicon-carbon spherical particles, and the conductivity of the graphite material with a larger particle size is poor, resulting in poor dynamic performance of the negative electrode sheet, which is not conducive to the cycle life of the battery; or the silicon-carbon material with a smaller particle size is prone to agglomeration and poor dispersibility. When d2 / d is too small (for example, less than 1.33), the particle size of the secondary graphite particles is too small relative to the particle size of the primary silicon-carbon spherical particles. The graphite material with a smaller particle size is not pressure-resistant, which affects the improvement of the compaction density of the negative electrode sheet and thus affects the energy density of the battery; or the silicon-carbon material with a larger particle size has poor conductivity, which affects the kinetic properties of the negative electrode sheet, and the particles are not pressure-resistant and easily broken.
[0065] In the present invention, the OI value V of the negative electrode active coating is OI The extension rate s of the negative electrode current collector in the first direction satisfies: 0.1≤V OI ×s≤2, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2. The first direction refers to the length direction of the negative electrode sheet.
[0066] In one example, 0.4 ≤ V OI ×s≤1.1.
[0067] The OI value of the negative electrode active coating represents the overall orientation of the negative electrode active material. The smaller the OI value, the smaller the expansion rate of the negative electrode active material in the thickness direction of the battery (ie, the Z axis). During the negative electrode sheet rolling process and the battery charging and discharging process, the expansion of the negative electrode active material in the horizontal direction (ie, the X axis or the Y axis) will drive the negative electrode collector to extend. When the expansion is large, if the elongation of the negative electrode collector is low at this time, the corresponding extension cannot occur, which will cause the original direction of the negative electrode active material particles to be misaligned, causing excessive expansion in the thickness direction (ie, the Z axis), which is not conducive to the cycle stability of the battery. Therefore, it is necessary to regulate the relationship between the two. When the OI value is small, the extension of the negative electrode active material in the horizontal direction is large, and the elongation of the negative electrode collector in the first direction needs to be increased simultaneously; when the OI value is large, the elongation of the negative electrode collector in the first direction can be reduced accordingly. When the two meet a specific relationship, the battery can further improve the cycle stability.
[0068] In the present invention, the OI value V of the negative electrode active coating is OI It may be 10-30.5, for example 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 or 30.5.
[0069] In one example, V OI It is 12-17.
[0070] In the present invention, the OI value V of the negative electrode active coating is OI It can be obtained by testing by conventional methods in the art, for example, after discharging the battery to 0% SOC, disassembling and removing the negative electrode sheet, soaking it in DMC solvent for 12 hours, and then rinsing it with DMC solvent to remove the lithium salt attached to the negative electrode sheet, using an X-ray powder diffraction instrument (such as Shimadzu XRD-6100) to test the negative electrode active coating to obtain a diffraction spectrum, and the intensity of the (004) peak at 2θ of 54°-55° is recorded as I 004 The intensity of the (110) peak with 2θ of 77°-78° is recorded as I 110 , V OI That is I 004 / I 110 .
[0071] In the present invention, the elongation s of the negative electrode current collector in the first direction may be 1%-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0072] In one example, s is 2.5%-6.5%.
[0073] In the present invention, the elongation s of the negative electrode current collector in the first direction can be obtained by testing by conventional methods in the art, for example, after discharging the battery to 0% SOC, disassembling and removing the negative electrode sheet, taking the empty foil area at the head (or tail), soaking it in DMC solvent for 12 hours, and then rinsing it with DMC solvent to remove the lithium salt attached to the empty foil area; after drying, using a cutter to cut the above-treated empty foil area into samples with a size of 15 mm along the width direction of the negative electrode current collector and a size of more than 50 mm along the length direction of the negative electrode current collector; using a WD-D3 electronic universal testing machine (with a precision of 0.5 level and an accuracy of ±1% of the indicated value), setting a gauge length of 50 mm and a speed of 50 mm / min, the above-mentioned sample is subjected to a tensile test along the length direction to measure the elongation s of the negative electrode current collector in the first direction.
[0074] In the present invention, the surface of the negative electrode active coating located on at least one side of the negative electrode current collector may have a first concave portion. The first concave portion is arranged on the surface of the negative electrode active coating, and the first concave portion can provide a certain release space for the volume expansion of the negative electrode active material, and can reduce the extension of the negative electrode current collector caused by the volume expansion of the negative electrode active material, which is conducive to further improving the cycle stability of the battery.
[0075] In the present invention, the first concave portion may include a concave hole or a groove. The first concave portion may be obtained by laser drilling or wire punching technology. When the first concave portion is a groove, the groove may be arranged continuously or in sections. Figure 3 FIG. 1 is a schematic diagram (top view) of a groove on the surface of a negative electrode sheet in an example of the present invention, wherein: Figure 3 (a) The grooves are arranged continuously; Figure 3 (b) The grooves are arranged in sections. As can be seen from the figure, the surface of the negative electrode sheet (i.e., the surface of the negative electrode active coating) has several grooves. Figure 3 In (a), the grooves are continuously arranged in the width direction of the negative electrode sheet. Figure 3 In (b), the grooves are arranged in sections in the width direction of the negative electrode sheet. Figure 3 Only the case where the groove is arranged along the width direction of the negative electrode sheet is given, and the groove can also be arranged along the length direction of the negative electrode sheet.
[0076] In the present invention, the depth of the first concave portion may be 5 μm-40 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm. The depth of the first concave portion has the conventional meaning in the art, and refers to the vertical distance from the lowest point in the first concave portion to the surface of the negative electrode sheet. The depth of the first concave portion can be obtained by testing by conventional methods in the art, for example, using a 3D profiler to test the depths of all first concave portions or at least 20 first concave portions on the surface of the negative electrode active coating, and taking an average value.
[0077] In one example, the depth of the first concave portion is 15 μm-31 μm.
[0078] In the present invention, the width of the first concave portion may be 40 μm-200 μm, for example, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 150 μm or 200 μm.
[0079] In one example, the width of the first concave portion is 60 μm-100 μm.
[0080] When the first recess is a recessed hole, the width of the first recessed portion refers to the aperture of the recessed hole. The aperture of the recessed hole has the conventional meaning in this field. When the shape of the orthographic projection of the recessed hole on the surface of the negative electrode sheet is a "regular circle", the aperture of the recessed hole is the diameter of the regular circle; when the shape of the orthographic projection of the recessed hole on the surface of the negative electrode sheet is a non-"regular circle" (such as an ellipse or an irregular curved polygon), the aperture of the recessed hole is the diameter of an equivalent circle with an area equal to that of the non-"regular circle". The aperture of the recessed hole can be obtained by conventional means in this field, such as by using a 3D profilometer, selecting all or at least 10 recessed holes, measuring the aperture, and taking the average value.
[0081] When the first concave portion is a groove, the width of the first concave portion refers to the width of the groove. The width of the groove has a conventional meaning in the art. The positive projection of the groove on the surface of the negative electrode sheet includes two long sides, and the width of the groove refers to the average distance from one long side to another long side in the length direction or width direction of the negative electrode sheet. Figure 4 FIG. 1 is a schematic diagram of the width of a groove in an example of the present invention, wherein Figure 4 (a)- Figure 4 The two long sides of the groove in (c) are straight lines. Figure 4 The two long sides of the groove in (d) are curved. Figure 4 (a) and Figure 4 In (b), the two long sides are arranged in parallel, so that in the width direction of the negative electrode sheet, the vertical distance from any point on one long side to the other long side is equal. In this case, the width of the groove is the vertical distance L1 from any point on one long side to the other long side in the length direction or width direction of the negative electrode sheet. Figure 4 In (c), the two long sides of the groove are straight lines, but they are not set in parallel. Therefore, in the width direction, the size from any point on one long side to the other long side is not equal. In this case, the width of the groove can be averaged, that is, on one long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width L1 corresponding to each point is measured, and the average value is taken to obtain the width of the groove. Figure 4 In (d), the two long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the width of the groove can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 4 In (d), the two long sides are curved and do not exist. Figure 4(c) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), and the width L1 corresponding to each point is measured, and the average value is taken to obtain the width of the groove. The width of the groove can be obtained by conventional means in the art, such as by using a 3D profiler to test the width of all grooves or at least 5 grooves on the surface of the negative electrode active coating and take the average value.
[0082] In the present invention, the spacing of the first recesses may be 0.5 mm-5 mm, for example, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm.
[0083] In one example, the interval between the first recesses is 0.8 mm-1.5 mm.
[0084] When the first concave portion is a concave hole, the spacing of the first concave portion refers to the spacing of the concave holes. The spacing of the concave holes has a conventional meaning in the art. It refers to the shortest distance between the edges of two adjacent concave holes on the surface of the negative electrode sheet. The spacing of the concave holes can be obtained by conventional means in the art, such as by selecting all or at least 10 groups of adjacent concave holes through a 3D profilometer, measuring the spacing, and taking the average value.
[0085] When the first concave portion is a groove, the spacing of the first concave portion refers to the spacing of the grooves. It is understood that when there is only one groove on the surface of the negative electrode sheet, there is no spacing of the grooves. The spacing of the grooves has the conventional meaning in the art, which refers to the average distance between the two adjacent long sides of two adjacent grooves in the length direction or width direction of the negative electrode sheet. Figure 5 FIG. 1 is a schematic diagram of the spacing of grooves in an example of the present invention, wherein Figure 5 (a) is the case where two adjacent long sides are straight and parallel. Figure 5 (b) is the case where two adjacent long sides are straight lines and not parallel. Figure 5 (c) is the case where two adjacent long sides are curved. Figure 5 In (a), the two adjacent long sides are straight and parallel, so in the width direction, the distance from any point on one long side to the other long side is equal. In this case, the spacing of the grooves is the distance L2 from any point on one long side to the other long side in the width direction. Figure 5In (b), the two adjacent long sides are straight lines, but they are not set in parallel. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the grooves can be averaged, that is, on a long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width L2 corresponding to each point is measured, and the average value is taken to obtain the spacing. Figure 5 In (c), the two adjacent long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the grooves can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 5 (c) The two long sides are curved, so there is no Figure 5 (b) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), and the width L2 corresponding to each point is measured, and the average value is taken to obtain the spacing. The spacing of the grooves can be obtained by conventional means in the art, such as by using a 3D profilometer to test the spacing of all grooves or at least 5 grooves on the surface of the negative electrode active coating and take the average value.
[0086] A second aspect of the present invention provides a lithium ion secondary battery, wherein the lithium ion secondary battery comprises the negative electrode sheet described in the first aspect of the present invention.
[0087] In the present invention, the lithium-ion secondary battery may further include a positive electrode sheet.
[0088] <Positive electrode>
[0089] In the present invention, the positive electrode sheet may include a positive electrode current collector and a positive electrode active coating located on at least one side of the positive electrode current collector. The length of the positive electrode active coating located on the first surface of the positive electrode current collector is greater than the length of the positive electrode active coating located on the second surface of the positive electrode current collector. It can be understood that when the positive electrode sheet is coated, there are single-sided coating areas and double-sided coating areas. The single-sided coating area is the positive electrode current collector located in the area, and only one side of the surface has the positive electrode active coating; while the double-sided coating area is the positive electrode current collector located in the area, and both sides of the surface have the positive electrode active coating. This leads to the situation that the lengths of the positive electrode active coatings on the two sides of the positive electrode sheet are not equal. In the present invention, the side with a relatively longer length of the positive electrode active coating on the surface of the positive electrode current collector is defined as the first surface, and the side with a relatively shorter length of the positive electrode active coating is defined as the second surface. The area where the projections of the positive electrode active coating located on the first surface and the positive electrode active coating located on the second surface overlap in the thickness direction of the positive electrode sheet is the double-sided coating area, and the area where the above projections do not overlap is the single-sided coating area. Due to the special structure of the wound battery, usually the first surface faces the winding center of the winding core, and the second surface faces away from the winding center of the winding core.
[0090] In the present invention, the surface of the positive electrode active coating on the first surface has a second recess, and the surface of the positive electrode active coating on the second surface has a protrusion. A structure with a recess on one side and a protrusion on the other side can be obtained by embossing the surface of the positive electrode sheet. The inventor of the present invention analyzed the forces on the positive electrode active coatings facing the winding center and away from the winding center in the core, and found that when a recess is provided on the first surface facing the winding center and a protrusion is provided on the second surface away from the winding center, it is not only beneficial to the structural stability of the positive electrode sheet itself; it can also provide a better buffer space for the volume expansion of the negative electrode sheet, and can improve the cycle life of the battery. As Figure 6 Shown in is a schematic structural diagram of a core in an example of the present invention. As can be seen from the figure, the surface of the positive electrode active coating on the first surface has a second recess, and the surface of the positive electrode active coating on the second surface has a protrusion. The first surface faces the winding center of the core, and the second surface is away from the winding center of the core.
[0091] In the present invention, the shapes of the positive projections of the second recess and the protrusion on the surface of the positive electrode sheet are not limited, and can be circular, elliptical, linear (including straight or wavy lines), polygonal and other shapes.
[0092] In the present invention, the positive electrode sheet includes a positive electrode tab welding area, a pasting area, and a blank foil area. The blank foil area refers to the area on the positive electrode current collector where the positive electrode active coating is not coated except for the positive electrode tab welding area. The pasting area includes a double-sided coating area and a single-sided coating area. As Figure 7 Shown in is a schematic structural diagram of a positive electrode sheet in an example of the present invention, where Figure 7 (a) is a top view, Figure 7 (b) is a cross-sectional view along the thickness direction. As can be seen from the figure, the positive electrode sheet includes a positive electrode tab welding area 3, a pasting area 4, and a blank foil area 5, where the pasting area 4 includes a double-sided coating area 10 and a single-sided coating area 20.
[0093] In one example, the second recess and the protrusion are located in the pasting area.
[0094] In one example, the second recess and the protrusion are located in the double-sided coating area.
[0095] In one example, the second recess and the protrusion are located in the pasting area and in the double-sided coating area.
[0096] In the present invention, the distance from the second recess to the edge of the positive electrode tab welding area is w1, 0 mm < w1 ≤ 10 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm.
[0097] In the present invention, the distance from the second recess to the edge of the first side of the paste application area is w2, where 2 mm ≤ w2 ≤ 40 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, 25 mm, 30 mm, 35 mm, or 40 mm. The first side is the side where the positive tab welding area is provided.
[0098] In the present invention, the distance from the second recess to the edge of the second side of the paste application area is w3, where 2 mm ≤ w3 ≤ 25 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, or 25 mm. The second side is the side opposite to the side where the positive tab welding area is provided.
[0099] In the present invention, the distance from the second recess to the edge of the third side of the paste application area is w4, where 0 mm < w4 ≤ 20 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, or 20 mm. The third side is the side of the paste application area close to the first winding end.
[0100] In the present invention, the distance from the second recess to the boundary line between the double-sided coating area and the single-sided coating area is w5, where 0 mm < w5 ≤ 20 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, or 20 mm.
[0101] By controlling w1, w2, w3, w4, and w5, it is possible to ensure that the positive electrode sheet does not shed powder, which is beneficial to improving the cycle life of the battery.
[0102] Such as Figure 8The figure shows a schematic top view of the first surface of the positive electrode sheet in an example of the present invention. It can be seen from the figure that the first surface has a plurality of second recesses 6, and the distance from the second recess 6 to the edge of the positive electrode tab welding area 3 is w1, the distance from the second recess 6 to the first edge of the paste coating area 4 is w2, the distance from the second recess 6 to the second edge of the paste coating area 4 is w3, the distance from the second recess 6 to the third edge of the paste coating area 4 is w4, and the distance from the second recess 6 to the boundary line between the double-sided coating area 10 and the single-sided coating area 20 is w5.
[0103] In the present invention, the depth of the second concave portion may be 3 μm-40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm. The height of the convex portion may be 3 μm-40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.
[0104] In one example, the depth of the second concave portion is 10 μm-30 μm, and the height of the convex portion is 10 μm-30 μm.
[0105] In the present invention, the depth of the second concave portion and the height of the convex portion have the conventional meanings in the art, and the depth of the second concave portion refers to the vertical distance from the lowest point in the second concave portion to the surface of the positive electrode sheet. The height of the convex portion refers to the vertical distance from the highest point on the convex portion to the surface of the positive electrode sheet. The depth of the second concave portion and the height of the convex portion can be obtained by testing by conventional methods in the art, for example, by using a 3D profilometer, at least 10 second concave portions and 10 convex portions are selected on the positive electrode sheet, the depth of each second concave portion and the height of the convex portion are measured, and the average values are taken respectively.
[0106] In the present invention, the width of the second concave portion may be 0.2 mm to 8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm. The width of the convex portion may be 0.2 mm to 8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.
[0107] In one example, the width of the second concave portion is 1 mm to 3 mm, and the width of the convex portion is 1 mm to 3 mm.
[0108] In the present invention, when the shape of the projection of the second concave portion in the thickness direction of the positive electrode sheet is a regular circle, the width of the second concave portion is the diameter of the regular circle; when the shape of the projection of the second concave portion in the thickness direction of the positive electrode sheet is a non-"regular circle", the width of the second concave portion is the equivalent diameter of a circle with an area equal to that of the irregular circle. Similarly, when the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is a regular circle, the width of the convex portion is the diameter of the regular circle; when the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is a non-"regular circle", the width of the convex portion is the equivalent diameter of a circle with an area equal to that of the irregular circle. The width of the second concave portion and the width of the convex portion can be obtained by conventional methods in the art, for example, by using a 3D profiler, selecting at least 10 second concave portions and 10 convex portions on the surface of the positive electrode sheet, measuring the width of each second concave portion and the width of the convex portion, and taking the average values respectively.
[0109] In the present invention, the spacing of the second concave portions may be 0.5 mm to 8 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm. The spacing of the convex portions may be 0.5 mm to 8 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.
[0110] In one example, the spacing between the second concave portions is 1 mm to 3 mm, and the spacing between the convex portions is 1 mm to 3 mm.
[0111] In the present invention, the spacing of the second concave portions refers to the shortest distance between the edges of the orthographic projections of two adjacent second concave portions on the surface of the positive electrode sheet, and similarly, the spacing of the convex portions refers to the shortest distance between the edges of the orthographic projections of two adjacent convex portions on the surface of the positive electrode sheet. The spacing of the second concave portions and the spacing of the convex portions can be obtained by testing by conventional methods in the art, for example, by using a 3D profilometer, selecting at least 10 groups of adjacent second concave portions and 10 groups of adjacent convex portions on the surface of the positive electrode sheet, measuring the spacing of each group of second concave portions and the spacing of each group of convex portions, and taking the average values respectively.
[0112] In the present invention, the positive electrode active coating comprises a positive electrode active material. The positive electrode active material comprises lithium cobalt oxide. The composition of the positive electrode active coating can be a conventional choice in the art.
[0113] In the present invention, the battery may further include a separator and an electrolyte. Both the separator and the electrolyte may be conventionally selected in the art.
[0114] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.
[0115] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0116] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.
[0117] The following examples are used to illustrate the lithium ion secondary battery of the present invention.
[0118] Example 1
[0119] Prepare the battery as follows:
[0120] (1) Preparation of positive electrode sheet
[0121] Lithium cobalt oxide, a positive electrode conductive agent (conductive carbon black) and a positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 97:1:2, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly to prepare a positive electrode slurry; the positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a positive electrode sheet with a thickness of 100 μm; a positive electrode tab welding area of a fixed size is set on the paste coating area of the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 20 mm), and a nickel tab is laser welded in the positive electrode tab welding area; after being rolled, embossing is performed from the first surface to the second surface in the double-sided coating area (and avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;
[0122] The width of the second recess is 3 mm, the depth is 30 μm, and the spacing is 3 mm; w1 is 7 mm, w2 is 27 mm, w3 is 15 mm, w4 is 7 mm, and w5 is 7 mm.
[0123] (2) Preparation of negative electrode sheet
[0124] A graphite material (artificial graphite, the average particle size d2 of the secondary particles is 11.8 μm), a silicon-carbon material (the number of primary spherical particles accounts for 0.52 of the total number of primary spherical particles and secondary spherical particles, the average particle size d of the primary spherical particles is 3.9 μm, the particle size D of the secondary spherical particles is 7.8 μm, the sphericity of the primary spherical particles is 0.95, and the mass content of element Si in the silicon-carbon material is 70%), a negative electrode conductor (carbon nanotubes), a negative electrode dispersant (lithium carboxymethyl cellulose) and a negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 85:12:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on the negative electrode current collector (I 111 / I 200 6.9) on both sides of the surface, after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;
[0125] Among them, the mass content of element Si in the negative electrode active coating is 8.4%. 111 / I 200 ) / (c×d) is 21.1; d2 / d is 3, V OI is 15.6, the extension rate s of the negative electrode collector in the first direction is 6.5%, V OI ×s is 1.01; the width of the groove is 80.1 μm, the depth is 20.1 μm, and the spacing is 1.2 mm.
[0126] (3) Preparation of electrolyte
[0127] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, propylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; fluoroethylene carbonate (FEC) and lithium hexafluorophosphate (LiPF6) are dissolved in the above-mentioned organic solvent to obtain an electrolyte; wherein the mass content c of FEC in the electrolyte is 30%, and the mass content of LiPF6 in the electrolyte is 12.5%.
[0128] (4) Preparation of batteries
[0129] The positive electrode sheet prepared in step (1), the separator (comprising a polyethylene base film with a thickness of 4 μm, a ceramic layer with a thickness of 2 μm on one side of the base film, a polymethyl methacrylate adhesive layer with a thickness of 0.5 μm on the other side of the base film, and a polyvinylidene fluoride + polymethyl methacrylate adhesive layer with a thickness of 2.5 μm on the outer surface of the ceramic layer) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core; and a battery is obtained through packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV.
[0130] Example 2
[0131] The method is carried out with reference to Example 1, except that step (1) and step (2) are specifically as follows:
[0132] (1) Preparation of positive electrode sheet
[0133] Lithium cobalt oxide, a positive electrode conductive agent (conductive carbon black) and a positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 97:1:2, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly to prepare a positive electrode slurry; the positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a positive electrode sheet with a thickness of 100 μm; a positive electrode tab welding area of a fixed size is set on the paste coating area of the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 15 mm), and a nickel tab is laser welded in the positive electrode tab welding area; after being rolled, embossing is performed from the first surface to the second surface in the double-sided coating area (and avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;
[0134] The width of the second recess is 2 mm, the depth is 20 μm, and the spacing is 2 mm; w1 is 5 mm, w2 is 20 mm, w3 is 10 mm, w4 is 5 mm, and w5 is 5 mm.
[0135] (2) Preparation of negative electrode sheet
[0136] A graphite material (artificial graphite, the average particle size d2 of the secondary particles is 14.8 μm), a silicon-carbon material (the number of primary spherical particles accounts for 0.78 of the total number of primary spherical particles and secondary spherical particles, the average particle size d of the primary spherical particles is 3.2 μm, the particle size D of the secondary spherical particles is 9.5 μm, the sphericity of the primary spherical particles is 0.8, and the mass content of element Si in the silicon-carbon material is 70%), a negative electrode conductive agent (carbon nanotubes), a negative electrode dispersant (lithium carboxymethyl cellulose) and a negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 85:12:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on the negative electrode current collector (I 111 / I 200 4.5) on both sides of the surface, after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;
[0137] Among them, the mass content of element Si in the negative electrode active coating is 8.4%. 111 / I 200 ) / (c×d) is 16.7; d2 / d is 4.6, VOI is 12.2, the extension rate s of the negative electrode collector in the first direction is 3.8%, V OI ×s is 0.46; the width of the groove is 60 μm, the depth is 15.6 μm, and the spacing is 0.8 mm.
[0138] Example 3
[0139] The method is carried out with reference to Example 1, except that step (1) and step (2) are specifically as follows:
[0140] (1) Preparation of positive electrode sheet
[0141] Lithium cobalt oxide, a positive electrode conductive agent (conductive carbon black) and a positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 97:1:2, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly to prepare a positive electrode slurry; the positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, and rolled to obtain a positive electrode sheet with a thickness of 100 μm; a positive electrode tab welding area of a fixed size is set on the paste coating area of the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 25 mm), and a nickel tab is laser welded in the positive electrode tab welding area; after being rolled, embossing is performed from the first surface to the second surface in the double-sided coating area (and avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;
[0142] The width of the second recess is 1 mm, the depth is 10 μm, and the spacing is 1 mm; w1 is 9 mm, w2 is 34 mm, w3 is 20 mm, w4 is 10 mm, and w5 is 10 mm.
[0143] (2) Preparation of negative electrode sheet
[0144] A graphite material (artificial graphite, the average particle size d2 of the secondary particles is 10.1 μm), a silicon-carbon material (the number of primary spherical particles accounts for 0.35 of the total number of primary spherical particles and secondary spherical particles, the average particle size d of the primary spherical particles is 4.9 μm, the particle size D of the secondary spherical particles is 10.6 μm, the sphericity of the primary spherical particles is 0.85, and the mass content of element Si in the silicon-carbon material is 70%), a negative electrode conductive agent (carbon nanotubes), a negative electrode dispersant (lithium carboxymethyl cellulose) and a negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 85:12:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on the negative electrode current collector (I 111 / I 2003) The two side surfaces are baked and rolled to obtain a negative electrode sheet with a thickness of 110 μm; a first concave portion (groove) is manufactured on the surface of the negative electrode sheet using a laser;
[0145] Among them, the mass content of element Si in the negative electrode active coating is 8.4%. 111 / I 200 ) / (c×d) is 7.3; d2 / d is 2.1, V OI is 16.8, the extension rate s of the negative electrode collector in the first direction is 2.5%, V OI ×s is 0.42; the width of the groove is 99.9 μm, the depth is 30.1 μm, and the spacing is 1.5 mm.
[0146] Example 4 Group
[0147] This group of examples is used to verify the influence of the change of "the mass content c of element Si in the negative electrode active coating".
[0148] This group of examples is carried out with reference to Example 1, except that c is regulated by changing the mass content of the graphite material and the silicon-carbon material in the negative electrode slurry, as follows:
[0149] In Example 4a, the mass ratio of graphite material, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder is 92:5:0.4:0.1:2.5, wherein c is 3.5%; (I 111 / I 200 ) / (c×d) is 50.5;
[0150] In Example 4b, the mass ratio of graphite material, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder is 82:15:0.4:0.1:2.5, wherein c is 10.5%; (I 111 / I 200 ) / (c×d) is 16.8;
[0151] In Example 4c, the mass ratio of graphite material, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder is 94:3:0.4:0.1:2.5, wherein c is 2.1%; (I 111 / I 200 ) / (c×d) is 84.2;
[0152] In Example 4d, the mass ratio of graphite material, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder is 75.5:21.5:0.4:0.1:2.5, wherein c is 15.05%; (I 111 / I 200 ) / (c×d) is 11.8.
[0153] Example 5 Group
[0154] This group of examples is used to verify the influence of the change of the "average particle size d of the primary spherical particles".
[0155] This group of examples is carried out with reference to Example 1, except that the average particle size d of the spherical particles is changed once, as follows:
[0156] Example 5a, d is 1.1 μm; wherein d2 / d is 10.7;
[0157] In Example 5b, d is 5.9 μm; wherein d2 / d is 2.
[0158] Example 6 Group
[0159] This group of embodiments is used to verify “(I 111 / I 200 ) / (c×d)”.
[0160] This group of examples is carried out with reference to Example 4a and Example 1, except that the average particle size d1 of the primary spherical particles and / or the I of the negative electrode current collector are changed. 111 / I 200 To regulate (I 111 / I 200 ) / (c×d), as follows:
[0161] Example 6a is carried out in accordance with Example 4a, except that d is 3.2 μm, (I 111 / I 200 ) / (c×d) is 61.6.
[0162] Example 6b is carried out in accordance with Example 1, except that d is 4.9 μm, I 111 / I 200 is 1.8; (I 111 / I 200 ) / (c×d) is 4.4.
[0163] Example 7 Group
[0164] This group of embodiments is used to verify the influence of the change of "surface density m of the negative electrode sheet".
[0165] This group of examples is carried out with reference to Example 1, except that the surface density m of the negative electrode sheet is regulated by changing the coating amount of the negative electrode slurry, as shown in Table 1 for details.
[0166] Example 8 Group
[0167] This group of embodiments is used to verify the impact of the change of "m×y".
[0168] This group of examples is carried out with reference to Example 1, except that m×y is regulated by changing the coating amount of the negative electrode slurry and the roller pressing pressure, as shown in Table 1 for details.
[0169] Example 9
[0170] This example is used to verify the impact of the change that "the silicon-carbon material is only primary spherical particles and does not contain secondary spherical particles".
[0171] The method is carried out in accordance with Example 1, except that all the silicon-carbon materials are primary spherical particles, that is, the number of primary spherical particles accounts for 1 of the total number of primary spherical particles and secondary spherical particles.
[0172] Example 10
[0173] This example is used to verify the influence of the change of "the sphericity of primary spherical particles".
[0174] The same process is carried out as in Example 1, except that the sphericity of the primary spherical particles is changed to 0.7.
[0175] Example 11 Group
[0176] This group of examples is used to verify the impact of changes in "the value of the number of primary spherical particles to the total number of primary spherical particles and secondary spherical particles".
[0177] This group of examples is carried out with reference to Example 1, except that the number ratio of spherical particles is changed once, as follows:
[0178] Example 11a, the number of primary spherical particles accounts for 0.12 of the total number of primary spherical particles and secondary spherical particles;
[0179] In Example 11b, the number of primary spherical particles accounts for 0.89 of the total number of primary spherical particles and secondary spherical particles.
[0180] Example 12
[0181] This example is used to verify the impact of "artificial graphite does not contain secondary particles".
[0182] The method is carried out in accordance with Example 1, except that the artificial graphite is a primary particle with an average particle size of 6.1 μm, wherein V OI 30.2, V OI ×s is 1.97.
[0183] Example 13 Group
[0184] This group of examples is used to verify the influence of the change of the "average particle size D of the secondary spherical particles".
[0185] This group of examples is carried out with reference to Example 1, except that the average particle size D of the secondary spherical particles is changed, as follows:
[0186] Example 13a, D is 8.3 μm, V OI 29, V OI ×s is 1.81;
[0187] Example 13b, D is 19.8 μm, V OI 10.4, V OI ×s is 0.64.
[0188] Example 14 Group
[0189] This group of examples is used to verify the "intensity of the 111 peak 111 The intensity of the peak with 200 200 The impact of changes in the ratio of .
[0190] This group of examples is carried out with reference to Example 1, except that the current collector of the negative electrode is changed to adjust the I 111 / I 200 , as follows:
[0191] Example 14a, I 111 / I 200 is 1.8, (I 111 / I 200 ) / (c×d) is 5.5, the extension rate s of the negative electrode collector in the first direction is 1.2%, V OI ×s is 0.19;
[0192] Example 14b, I 111 / I 200 =10, (I 111 / I 200 ) / (c×d) is 30.5, the extension rate s of the negative electrode collector in the first direction is 9.9%, V OI ×s is 1.54.
[0193] Embodiment 15
[0194] This embodiment is used to verify the OI ×s” changes.
[0195] The same method as in Example 2 is used, except that the V OI ×s, as follows:
[0196] Changing the negative electrode current collector, I 111 / I 200 is 3, s is 2.5%, V OI ×s is 0.31.
[0197] Example 16
[0198] This embodiment is used to verify the influence of changing the “type of the first recess”.
[0199] The process is carried out in accordance with Example 1, except that a laser is used to make recessed holes on the surface of the negative electrode sheet, wherein the width of the recessed holes is 80.1 μm, the depth is 25.2 μm, and the spacing is 0.5 mm.
[0200] Embodiment 17
[0201] This embodiment is used to verify the influence of “no first recess is provided on the surface of the negative electrode active coating”.
[0202] The same procedure is carried out as in Example 1, except that no groove is made on the surface of the negative electrode sheet.
[0203] Embodiment 18
[0204] This example is used to verify the influence of “no second concave portion and convex portion being provided on the surface of the positive electrode active coating layer”.
[0205] The same process is carried out as in Example 1, except that no embossing treatment is performed.
[0206] Embodiment 19
[0207] This example is used to verify the influence of “whether the second concave portion is located on the surface of the positive electrode active coating on the first surface and whether the convex portion is located on the surface of the positive electrode active coating on the second surface”.
[0208] The method is carried out in accordance with Example 1, except that the embossing treatment is performed from the second surface to the first surface, that is, the surface of the positive electrode active coating on the second surface has a second concave portion, and the surface of the positive electrode active coating on the first surface has a convex portion.
[0209] Embodiment 20
[0210] This embodiment is used to verify the influence of "whether the single-sided coating area has a second concave portion".
[0211] The process is carried out in accordance with Example 1, except that embossing is performed on the single-sided coating area and the double-sided coating area (avoiding the positive electrode tab welding area).
[0212] Example 21 Group
[0213] This group of embodiments is used to verify the impact of changes in "w1, w2, w3, w4 and w5".
[0214] This group of examples is carried out with reference to Example 1, except that w1, w2, w3, w4 and w5 are changed as follows:
[0215] In embodiment 21a, w1 is 0.5 mm, w2 is 2 mm, w3 is 2 mm, w4 is 0.5 mm, and w5 is 0.5 mm;
[0216] In Example 21b, w1 is 10 mm, w2 is 40 mm, w3 is 25 mm, w4 is 20 mm, and w5 is 20 mm.
[0217] Except for Example 18, the convex portions of the above embodiments all meet the following requirements: a height of 3 μm-40 μm, a width of 0.2 mm-8 mm, and a spacing of 0.5 mm-8 mm.
[0218] Test Case I
[0219] Areal density and compacted density
[0220] After the battery prepared in the example was discharged to 0% SOC, the negative electrode sheet was disassembled and taken out, and the surface density and compaction density of the negative electrode sheet were tested. The results are recorded in Table 1.
[0221] Table 1
[0222]
[0223]
[0224] Comparative Example 1
[0225] The method is carried out with reference to Example 1, except that the mass ratio of the graphite material, the silicon-carbon material, the negative electrode conductive agent, the negative electrode dispersant and the negative electrode binder is 65.5:31.5:0.4:0.1:2.5, wherein the mass content of element Si in the negative electrode active coating is 22%.
[0226] Comparative Example 2
[0227] This group of comparative examples is used to verify the influence of the change of the "average particle size d1 of the primary spherical particles".
[0228] This comparative example is carried out with reference to Example 1, except that the average particle size d1 of the spherical particles is changed, as follows:
[0229] Comparative Example 2a, d1 is 0.8 μm;
[0230] In Comparative Example 2b, d1 is 6.5 μm.
[0231] Test Case
[0232] (1) Volume energy density test
[0233] The battery was charged to the upper voltage limit (4.48V) at a current of 0.2C, then charged at a constant voltage until the current dropped to 0.02C, and then discharged at a current of 0.2C to 3.0V, with the discharged energy recorded as E; the thickness, width and length of the battery were measured and the product of the three was calculated to obtain the volume of the battery recorded as V. The calculation formula for volume energy density is VED = E / V, and the results are recorded in Table 2.
[0234] (2) 45℃ high temperature cycle test and negative electrode current collector tensile strength test
[0235] Place it in a constant temperature room at 45℃ for 2h, charge it to 4.25V at 3C constant current, then charge it to 4.48V at 2.5C constant current and constant voltage, stop at 0.05C, and place it for 10min; then discharge it to 3.0V at 0.7C, and cycle it for 500 times. The thickness of the battery at the 500th cycle is h1, and the thickness of the battery at the first full charge is h0. (h1-h0) / h0 is the thickness expansion rate after 500 cycles. After 500 cycles, discharge the battery at 0.2C to 2.75V, disassemble the battery, take out the negative electrode sheet, soak it in DMC solvent for 12h, and then rinse it with DMC solvent to remove air. The lithium salt attached to the foil area was soaked in deionized water to make the negative electrode active coating on its surface fall off naturally; after it was completely fallen off, the negative electrode collector was dried, and the empty foil area after the above treatment was cut into samples with a size of 15 mm along the width direction of the negative electrode collector and a size of more than 50 mm along the length direction of the negative electrode collector using a cutter; a WD-D3 electronic universal testing machine (with a precision of 0.5 level and an accuracy of ±1% of the indicated value) was used to set the gauge length to 50 mm and the speed to 50 mm / min, and the above samples were subjected to a tensile test along the length direction to measure the tensile strength of the negative electrode collector in the first direction, and the results are recorded in Table 2.
[0236] Table 2
[0237]
[0238]
[0239] As can be seen from Table 2, the battery prepared by the negative electrode sheet of the present invention has a higher energy density and a lower thickness expansion rate than the comparative example, and after cycling, the tensile strength of the negative electrode current collector is higher. Among them, the surface density of Example 7a is lower than that of Example 1, and the cycle capacity retention rate of Example 7a is higher than that of Example 1; while the surface density of Example 7b is higher than that of Example 1, and the cycle capacity retention rate of Example 7b is lower than that of Example 1. The average particle size of the secondary particles of graphite in Example 13b is larger, so Example 13b has a higher risk of lithium precipitation than Example 1.
[0240] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector, wherein the negative electrode active coating comprises a negative electrode active material; the negative electrode active material comprises a silicon-carbon material; the silicon-carbon material comprises primary spherical particles; The mass content c of element Si in the negative electrode active coating is 1.5%-15.5%; The average particle size d of the primary spherical particles is 1 μm-6 μm; The negative electrode current collector includes Cu, and the XRD diffraction spectrum of the negative electrode current collector has a 111 peak at 2θ of 42.5°-44.5° and a 200 peak at 2θ of 49°-52°, and the intensity of the 111 peak is I 111 , the intensity of the 200 peak is I 200 ;I 111 / I 200 Is 1-10.
2. The negative electrode sheet according to claim 1, wherein: c is 3.5%-10.5%; and / or, d is 3 μm-5 μm; and / or 111 / I 200 3-6.9; And / or, the silicon-carbon material includes a material formed by filling silicon and / or oxidized silicon in pores of porous carbon; and / or, c, d, I 111 and I 200 Satisfy: 5≤(I 111 / I 200 ) / (c×d)≤85; preferably, 7.3≤(I 111 / I 200 ) / (c×d)≤50.5; And / or, the mass content of element Si in the silicon-carbon material is 30%-80%.
3. The negative electrode sheet according to claim 1 or 2, wherein: The surface density of the negative electrode sheet is m, in mg / cm 2 The compaction density of the negative electrode sheet is y, in g / cm 3 ; m and y satisfy: 6.5≤m×y≤13; preferably, 9.6≤m×y≤9.9; and / or, m is 5-8, unit is mg / cm 2 ; and / or, y is 1.35-1.6, in g / cm 3 .
4. The negative electrode sheet according to claim 1 or 2, wherein: The silicon-carbon material further includes secondary spherical particles formed from the primary spherical particles; Preferably, the average particle size D of the secondary spherical particles is 3 μm-20 μm; more preferably 7.5 μm-11 μm; Preferably, the sphericity of the primary spherical particles is 0.7-1; more preferably 0.8-0.95; Preferably, in the negative electrode active coating, the amount of the primary spherical particles accounts for 0.1-0.9 of the total amount of the primary spherical particles and the secondary spherical particles; more preferably, 0.35-0.
8.
5. The negative electrode sheet according to claim 1 or 2, wherein: The negative electrode active material further includes a graphite material, and the graphite material includes secondary particles; Preferably, the average particle size d2 of the secondary particles is 6 μm-20 μm; more preferably 10 μm-15 μm; Preferably, the ratio of the average particle size d2 of the secondary particles to the average particle size d of the primary spherical particles is 1.33≤d2 / d≤20; more preferably, 2.1≤d2 / d≤4.
6.
6. The negative electrode sheet according to claim 1 or 2, wherein: The OI value V of the negative electrode active coating OI The extension rate s of the negative electrode current collector in the first direction satisfies: 0.1≤V OI ×s≤2, the first direction refers to the length direction of the negative electrode sheet; preferably, 0.4≤V OI ×s≤1.1; And / or, the OI value V of the negative electrode active coating OI 10-30.5; preferably 12-17; And / or, the elongation s of the negative electrode current collector in the first direction is 1%-10%, preferably 2.5%-6.5%.
7. The negative electrode sheet according to claim 1 or 2, wherein: The surface of the negative electrode active coating layer located on at least one side of the negative electrode current collector has a first concave portion; Preferably, the depth of the first concave portion is 5 μm-40 μm; Preferably, the width of the first concave portion is 40 μm-200 μm; Preferably, the spacing between the first recesses is 0.5 mm-5 mm.
8. A lithium ion secondary battery, characterized in that: The lithium-ion secondary battery comprises the negative electrode sheet according to any one of claims 1 to 7.
9. The lithium ion secondary battery according to claim 8, wherein: The lithium-ion secondary battery further comprises a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active coating located on at least one side of the positive electrode current collector; the length of the positive electrode active coating located on the first surface of the positive electrode current collector is greater than the length of the positive electrode active coating located on the second surface of the positive electrode current collector; The area where the projections of the positive electrode active coating on the first surface and the positive electrode active coating on the second surface in the thickness direction of the positive electrode sheet overlap is a double-sided coating area, and the area where the projections do not overlap is a single-sided coating area; The surface of the positive electrode active coating layer located on the first surface has a second concave portion, and the surface of the positive electrode active coating layer located on the second surface has a convex portion; Preferably, the positive electrode sheet includes a coating area, the coating area includes the double-sided coating area and the single-sided coating area, and the second recess and the protrusion are located in the double-sided coating area; Preferably, the positive electrode sheet includes a positive electrode tab welding area, a coating area, and a blank foil area, and the second recess and the protrusion are located in the coating area; Preferably, the depth of the second recess is 3 μm - 40 μm, the width of the second recess is 0.2 mm - 8 mm, and the spacing of the second recess is 0.5 mm - 8 mm; Preferably, the height of the protrusion is 3 μm - 40 μm, the width of the protrusion is 0.2 mm - 8 mm, and the spacing of the protrusion is 0.5 mm - 8 mm.
10. The lithium ion secondary battery according to claim 9, wherein The positive electrode sheet includes a positive electrode tab welding area, a coating area, and a blank foil area, and the coating area includes the double-sided coating area and the single-sided coating area; The distance from the second recess to the edge of the positive electrode tab welding area is w1, where 0 mm < w1 ≤ 10 mm; And / or, the distance from the second recess to the edge of the first side of the coating area is w2, where 2 mm ≤ w2 ≤ 40 mm, and the first side is the side where the positive electrode tab welding area is provided; And / or, the distance from the second recess to the edge of the second side of the coating area is w3, where 2 mm ≤ w3 ≤ 25 mm, and the second side is the side opposite to the side where the positive electrode tab welding area is provided; And / or, the distance from the second recess to the edge of the third side of the coating area is w4, where 0 mm < w4 ≤ 20 mm, and the third side is the side of the coating area close to the starting end of winding; And / or, the distance from the second recess to the boundary line between the double-sided coating area and the single-sided coating area is w5, where 0 mm < w5 ≤ 20 mm.
Citation Information
Cited By
Negative electrode sheet and lithium-ion secondary battery
WO2026145181A1